Đặc điểm địa hóa khoáng vật quặng Mangan vùng mỏ Tốc Tát - Anh, Đào Duy (Vietnam Journal of Earth Sciences, 2012)
SUMMARYGeochemical-mineralogical characteristics of manganese ores in the Toc Tat areaToc Tat manganese deposit is of neritic origin, the manganese ores were formed by sedimentary process and alterated by later weathering process. Using many modern methods, this research presents in detail geochemical-mineralogical characteristics of manganese ores in the Toc Tat area. The manganese minerals include pyrolusite, hollandite and mangannite as the main minerals ; and jacobsite, bixbyite, hausmanniteand braunite as the minor minerals. Besides, the gangue minerals include hematite, magnetite, goethite, quartz, calcite, apatite and feldspar. Theywere intergrown at even micro scale and formed complex mineral assemblages